Suicide in Hong Kong during the COVID-19 pandemic: an observational study - Yu Jiang; Anying Bai; Jinjian Li; Yuhang Pan (BMJ Public Health)
Introduction The COVID-19 pandemic has exacerbated suicide risk factors in Hong Kong, which faces economic shocks and strict travel restrictions due to its unique economic structure and geographical location. However, there is a scarcity of reliable empirical evidence regarding the relationship between the pandemic and suicide mortality. This study examines whether changes in the suicide rate align with COVID-19 situations and anti-COVID-19 policy events in Hong Kong, focusing on vulnerable population groups based on demographic and socioeconomic characteristics.Methods Suicide data spanning 1 January 2019 to 31 December 2022 were sourced from the Hong Kong Suicide Press Database. Case-level data were aggregated monthly by district. Population-weighted Poisson regression with district-level fixed effects was employed to analyse suicide patterns and their association with COVID-19 developments. Robustness checks and demographic-based heterogeneity analysis were conducted, distinguishing suicide risk among different population groups.Results A total of 4061 suicide cases were analysed, encompassing deaths and attempts. The first wave of the pandemic saw a 30% decline in suicide cases compared with the 2019 average, while the second and fifth waves witnessed increases of 33% and 51% in suicide rates, respectively. Older adults and individuals with lower socioeconomic status were particularly susceptible to the adverse effects, as evidenced by a significant rise in suicides during the fifth wave.Conclusions The findings underscore the importance of targeted interventions to address the mental health needs of vulnerable populations during pandemics, highlighting the impact of COVID-19 situations and antipandemic policies on the suicide rate.